Global English slang : methodologies and perspectives - Coleman, Julie (New York : Routledge, 2014)
'Global English Slang brings together twenty key international experts and provides a timely and essential overview of English slang around the world today.The book illustrates the application of a range of different methodologies to the study of slang and demonstrates the interconnection between the different sub-fields of linguistics.A key argument throughout is that slang is a function played by specific words or phrases rather than a characteristic inherent in the words themselves- what is slang in one context is not slang in another. The volume also challenges received wisdom on the nature of slang: that it is short-lived and that slang is restricted to verbal language.With an introduction by editor Julie Coleman, the topics covered range from Inner City New York slang and Hip Hop Slang to UK student slang and slang in Scotland. Authors also explore slang in Jamaica, Australia, New Zealand, India and Hong Kong and the influence of English slang on Norwegian, Italian and Japanese. A final section looks at slang and new media including online slang usage, and the possibilities offered by the internet to document verbal and gestural slang. Global English Slang is an essential reference for advanced undergraduates, postgraduates and researchers working in the areas of lexicology, slang and World Englishes'--
Keywords: English language -- Slang; English language -- Usage; English language -- Spoken English